Risk perception of sexually transmitted infections and HIV in Nigerian commercial sex workers in Barcelona: a qualitative study. Issue 6 (15th June 2015) - Coma Auli, Núria; Mejía-Lancheros, Cília; Berenguera, Anna; Pujol-Ribera, Enriqueta
Abstract : Objective: This study aimed to determine in detail the risk perception of sexually transmitted infections (STIs) and HIV, and the contextual circumstances, in Nigerian commercial sex workers (CSWs) in Barcelona. Design: A qualitative study with a phenomenological approach. Setting: Raval area in Barcelona. Participants: 8 CSWs working in Barcelona. Methods: A phenomenological study was carried out with Nigerian CSWs in Barcelona. Sampling was theoretical, taking into account: different age ranges; women with and without a partner; women with and without children; and women participating or not in STI/HIV-prevention workshops. Information was obtained by means of eight semistructured individual interviews. An interpretative content analysis was conducted by four analysts. Results: Illegal immigrant status, educational level, financial situation and work, and cultural context had mixed effects on CSW knowledge of, exposure to, and prevention and treatment of STI and HIV. CSWs were aware of the higher risk of STI associated with their occupation. They identified condoms as the best preventive method and used them during intercourse with clients. They also implemented other preventive behaviours such as personal hygiene after intercourse. Control of sexual services provided, health education and healthcare services had a positive effect on decreasing exposure and better management of STI/HIV. Conclusions: Nigerian CSWs are a vulnerable group because of their poor socioeconomic status. The perception of risk in this group and their preventive behaviours are based on personal determinants, beliefs and experiences from their home country and influences from the host country. Interventions aimed at CSWs must address knowledge gaps, risk behaviours and structural elements.